Analysis of genome-wide association studies of low-temperature germination in Xian and Geng rice - Li, Kang; Hassan, Muhammad Ahmad; Guo, Jinmeng; Zhao, Xueyu; Gan, Quan; Lin, Cuixiang; Ten, Bin; Zhou, Kunneng; Li, Min; Shi, Yingyao; Ni, Dahu; Song, Fengshun (Frontiers in Plant Science, 2024)
Rice is the leading global staple crop. Low temperatures pose negative impacts on rice's optimal growth and development. Rice cultivars acclimating to low temperatures exhibited improved seedling emergence under direct-seeded sowing conditions, yet little is known about the genes that regulate germination at low temperatures (LTG). In this research investigation, we've performed whole genome sequencing for the 273 rice plant materials. Using the best linear unbiased prediction (BLUP) values for each rice material, we identified 7 LTG-related traits and performed the efficient genetic analysis and genome-wide association study (GWAS). As a result of this, 95 quantitative trait loci (QTLs) and 1001 candidate genes associated with LTG in rice were identified. Haplotype analysis and functional annotation of the candidate genes resulted in the identification of three promising candidate genes (LOC_Os08g30520 for regulating LTG4 and LTG5, LOC_Os10g02625 for regulating LTG6, LTg7 and LTG8, and LOC_Os12g31460 for regulating LTG7, LTg8 and LTG9) involving in the regulation of LTG in rice. This research provides a solid foundation for addressing the LTG issue in rice and will be valuable in future direct-seeded rice breeding programs.